2004
DOI: 10.1111/j.1464-5491.2004.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for diabetes in Ho Chi Minh City, Vietnam

Abstract: This study found that the age, sex-adjusted prevalence of diabetes and IFG in Ho Chi Minh City were 3.8 and 2.5%, respectively, a rapid increase in the recent decade. Our study also indicates that ageing, a high WHR level, overweight and a sedentary lifestyle may be important determinants of the increased prevalence of diabetes during this transition period in Vietnam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 23 publications
8
38
3
Order By: Relevance
“…5 20 However, the prevalence was only 4% in Viet Nam, perhaps due to differences in climate or dietary habits. 19 We also found that the prevalence of prediabetes was slightly lower among urban than rural residents (19% versus 24%, respectively), as was observed in a study in China. 7 In contrast, the prevalence of diabetes was significantly higher among urban than rural residents (15% versus 8%, P < 0.001).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…5 20 However, the prevalence was only 4% in Viet Nam, perhaps due to differences in climate or dietary habits. 19 We also found that the prevalence of prediabetes was slightly lower among urban than rural residents (19% versus 24%, respectively), as was observed in a study in China. 7 In contrast, the prevalence of diabetes was significantly higher among urban than rural residents (15% versus 8%, P < 0.001).…”
Section: Discussionsupporting
confidence: 59%
“…32 Moreover, studies from both developing and developed countries have found inverse associations between diabetes and educational level and household socioeconomic status, perhaps because the better-educated were more health-conscious. 19,[33][34][35] However, obesity appears to be an independent risk factor for diabetes and a study from Brazil showed that better-educated and wealthier individuals were more likely to be obese. 36 Several other studies in developing countries also showed that the risk of obesity and diabetes increased with socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have examined the prevalence of type 2 diabetes and its risk factors in Vietnam [6,7], where type 2 diabetes and obesity are increasingly becoming public health concerns. A difficult aspect of estimating the prevalence of type 2 diabetes is that the disease is often asymptomatic at onset and can remain undiagnosed for several years [7,8], such that in the developed world approximately 50% of individuals with type 2 diabetes are undiagnosed [9].…”
Section: Introductionmentioning
confidence: 99%
“…A difficult aspect of estimating the prevalence of type 2 diabetes is that the disease is often asymptomatic at onset and can remain undiagnosed for several years [7,8], such that in the developed world approximately 50% of individuals with type 2 diabetes are undiagnosed [9]. However, universal screening is not cost-effective or recommended.…”
Section: Introductionmentioning
confidence: 99%